2012
DOI: 10.1103/physrevlett.108.218301
|View full text |Cite
|
Sign up to set email alerts
|

What Phasons Look Like: Particle Trajectories in a Quasicrystalline Potential

Abstract: Among the distinctive features of quasicrystals-structures with long-range order but without periodicity-are phasons. Phasons are hydrodynamic modes that, like phonons, do not cost free energy in the long-wavelength limit. For light-induced colloidal quasicrystals, we analyze the collective rearrangements of the colloids that occur when the phasonic displacement of the light field is changed. The colloidal model system is employed to study the link between the continuous description of phasonic modes in quasic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 24 publications
(23 reference statements)
1
48
0
Order By: Relevance
“…Experiments and computational studies have shown that in the absence of a drive, a variety of orderings can arise for colloidal particles interacting with one-dimensional (1D) periodic substrates [13,32,33], two-dimensional (2D) periodic substrates [15,20,21,[34][35][36][37][38], 2D quasiperiodic substrates [39][40][41][42][43], or 2D random substrates [44]. While these studies have provided a better understanding of several features of commensurateincommensurate behaviors, being able to dynamically control the particle ordering and dynamics could lead to a variety of applications, including self-assembled structures, particle separation, and photonic crystals.…”
Section: Introductionmentioning
confidence: 99%
“…Experiments and computational studies have shown that in the absence of a drive, a variety of orderings can arise for colloidal particles interacting with one-dimensional (1D) periodic substrates [13,32,33], two-dimensional (2D) periodic substrates [15,20,21,[34][35][36][37][38], 2D quasiperiodic substrates [39][40][41][42][43], or 2D random substrates [44]. While these studies have provided a better understanding of several features of commensurateincommensurate behaviors, being able to dynamically control the particle ordering and dynamics could lead to a variety of applications, including self-assembled structures, particle separation, and photonic crystals.…”
Section: Introductionmentioning
confidence: 99%
“…2. The diagrams correspond to those obtained for the D = 4 quasicrystals in [16,20]. The procedure to derive a trajectory for the case v = 0 (see Fig.…”
Section: Analyzing Colloidal Trajectories 41 Methodsmentioning
confidence: 99%
“…In a quasicrystal, we can map all particle positions onto particles inside characteristic areas of small phononic and phasonic displacements [16,20]. To determine the characteristic areas, we rst calculate phononic and phasonic displacements ∆u, ∆v and ∆w that change the dierences between the phases φ j − φ k in Eq.…”
Section: Characteristic Displacements and Characteristic Areasmentioning
confidence: 99%
See 2 more Smart Citations